Karakter Budaya Gua Kidang Hunian Prasejarah Kawasan Karst Pegunungan Utara Jawa - Indah Asikin Nurani (Balai Arkeologi Sumatera Utara, 2016)
AbstractThus far the karst area of the Northern Mountains of Java only has very few traces of occupation caves. investigations carried out by foreign researchers, particularly the ones from the Dutch, cover a number of caves in Situbondo, Tuban, and Bojonegoro. The interpretation made in relation to the results of investigations in the karst area of the Northern Mountains of Java show the distinct characteristics of maritime culture, which are artifacts and ecofacts, including marine and freshwater fauna. Aside from that, vertebrates were also found as artifacts and ecofacts. The cultural characteristics of habitation caves in the karst area of the Northern Mountains of Java differ from those in the Southern Mountains of Java, particularly Gunung Sewu (Thousand Mountains). Gua Kidang (Kidang Cave) is located in the karst area of Blora, and until now it is the only cave which shows indications that it was intensively inhabited for a long period of time. The cultural remains at that cave provide comprehensive information about the human occupation in their effort to survive. This article tries to reconstruct the living pattern of the inhabitants of Gua Kidang in exploring the surrounding environment to find food sources and raw materials to make their daily implements. The studies to reveal the problems include technological, geoarchaeological, and palaeoanthropological studies. This research employs descriptive-explanative method with inductive reasoning, while the approach is spatial archaeology. AbstrakKawasan karst pegunungan utara Jawa selama ini minim jejak budaya gua hunian. Penelitian yang telah dilakukan oleh peneliti asing khususnya orang Belanda, meliputi gua-gua di Situbondo, Tuban, dan Bojonegoro. interpretasi yang disusun sehubungan dengan hasil penelitian di kawasan karst Pegunungan Utara Jawa memberikan kekhasan karakter budaya pantai yaitu temuan baik artefak maupun ekofak dari fauna marin dan air tawar. Selain itu, fauna vertebrata juga ditemukan baik sebagai artefak maupun ekofak. Hal yang menjadi karakter budaya gua hunian di kawasan karst Pegunungan Utara Jawa berbeda dengan di kawasan karst Pegunungan Selatan Jawa khususnya di Gunung Sewu. Gua Kidang berada di kawasan karst Blora, yang sampai saat ini merupakan satu-satunya gua yang membuktikan indikasi dihuni secara intensif dalam kurun waktu yang panjang. Jejak budaya yang ditinggalkan memberikan informasi lengkap tentang okupasi manusia penghuninya dalam mempertahankan hidup. Tulisan ini akan memberikan gambaran rekonstruksi pola hidup manusiapenghuni Gua Kidang dalam mengeksplorasi alam sekitarnya, baik dalam mencari sumber makan maupun sumber bahan baku untuk peralatan sehari-hari. Kajian untuk mengungkap permasalahan meliputi kajian teknologi, geoarkeologi, dan paleoantropologi. Tulisan ini menggunakan metode deskriptif – eksplanatif dengan penalaran induktif. Pendekatan yang digunakan adalah arkeologi keruangan.